InterCarb: A Community Effort to Improve Interlaboratory Standardization of the Carbonate Clumped Isotope Thermometer Using Carbonate Standards. (24th May 2021) - Bernasconi, S. M.; Daëron, M.; Bergmann, K. D.; Bonifacie, M.; Meckler, A. N.; Affek, H. P.; Anderson, N.; Bajnai, D.; Barkan, E.; Beverly, E.; Blamart, D.; Burgener, L.; et al.
Abstract: Increased use and improved methodology of carbonate clumped isotope thermometry has greatly enhanced our ability to interrogate a suite of Earth‐system processes. However, interlaboratory discrepancies in quantifying carbonate clumped isotope (Δ47 ) measurements persist, and their specific sources remain unclear. To address interlaboratory differences, we first provide consensus values from the clumped isotope community for four carbonate standards relative to heated and equilibrated gases with 1, 819 individual analyses from 10 laboratories. Then we analyzed the four carbonate standards along with three additional standards, spanning a broad range of δ 47 and Δ47 values, for a total of 5, 329 analyses on 25 individual mass spectrometers from 22 different laboratories. Treating three of the materials as known standards and the other four as unknowns, we find that the use of carbonate reference materials is a robust method for standardization that yields interlaboratory discrepancies entirely consistent with intralaboratory analytical uncertainties. Carbonate reference materials, along with measurement and data processing practices described herein, provide the carbonate clumped isotope community with a robust approach to achieve interlaboratory agreement as we continue to use and improve this powerful geochemical tool. We propose that carbonate clumped isotope data normalized to the carbonate reference materials described in this publication should be reported as Δ47 (I‐CDES) values for Intercarb‐Carbon Dioxide Equilibrium Scale. Key Points: The exclusive use of carbonate reference materials is a robust method for the standardization of clumped isotope measurements Measurements using different acid temperatures, designs of preparation lines, and mass spectrometers are statistically indistinguishable We propose new consensus values for a set of seven carbonate reference materials and updated guidelines to report clumped isotope measurements